(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Mopolo Esa Village is one of the villages in Ranoyapo Subdistrict, South Minahasa Regency, North Sulawesi Province, located approximately 2.5 km from the subdistrict capital and flanked by two small rivers, the Sinduan and Oasaan. The total area of Mopolo Esa Village is divided into residential areas (18 ha), plantations (600 ha), rice fields (300 ha), and forests (482 ha), with a total area of 1,400 ha. Currently, in Mopolo Esa Village, there are several houses that are unfit for habitation scattered across 4 hamlets. The main objective of this community service is the construction of decent houses that are unfit for habitation, which do not meet safety and health standards for habitation or are in accordance with the government program called Unfit Houses. A problem in the construction of these decent houses is the lack of knowledge among those involved in the construction process, both the homeowners and the builders, about the principles and methods of building decent houses that meet the construction requirements recommended by the government. The method applied was through a survey, going directly to the village of Mopolo Esa to collect data from the community. Then, together with the village government, they provided assistance, starting from the process of drafting plans, selecting materials, to the process of proposing the right technology for repairing the houses themselves. The result showed that the community’s knowledge and awareness of structural and sanitation standards for livable houses increased, preparing them to implement the government’s program (RLH) in the future